Computer programming languages in practice : made simple computerbooks - Hofeditz, Calvin A. (Heinemann, 1985)
Computer Programming Languages in Practice provides an overview of various computer programming languages. The book begins with the fundamentals: what programs are; how they are planned and organized; what elements of the computer the programmer controls; flowcharting; and how computer data is organized. It then discusses material common to all languages, including the entry program, the compiler, the run-time system, syntax diagrams, and coding forms. The largest portion of this book is devoted to two very popular languages-BASIC and COBOL. It provides a brief history of the language's develo.